Mesenchymal Stem Cell-Derived Exosomes: Toward Cell-Free Therapeutic Strategies in Chronic Kidney Disease - Cao, Qinghua; Huang, Chunling; Chen, Xin-Ming; Pollock, Carol A. (Frontiers in Medicine, 2022)
Chronic kidney disease (CKD) is rising in global prevalence and has become a worldwide public health problem, with adverse outcomes of kidney failure, cardiovascular disease, and premature death. However, current treatments are limited to slowing rather than reversing disease progression or restoring functional nephrons. Hence, innovative strategies aimed at kidney tissue recovery hold promise for CKD therapy. Mesenchymal stem cells (MSCs) are commonly used for regenerative therapy due to their potential for proliferation, differentiation, and immunomodulation. Accumulating evidence suggests that the therapeutic effects of MSCs are largely mediated by paracrine secretion of extracellular vesicles (EVs), predominantly exosomes. MSC-derived exosomes (MSC-Exos) replicate the functions of their originator MSCs via delivery of various genetic and protein cargos to target cells. More recently, MSC-Exos have also been utilized as natural carriers for targeted drug delivery. Therapeutics can be effectively incorporated into exosomes and then delivered to diseased tissue. Thus, MSC-Exos have emerged as a promising cell-free therapy in CKD. In this paper, we describe the characteristics of MSC-Exos and summarize their therapeutic efficacy in preclinical animal models of CKD. We also discuss the potential challenges and strategies in the use of MSC-Exos-based therapies for CKD in the future.